Profile of Physical Fitness in Student Football Athletes Through Vo2 Max and FVC Lung Parameters in Sons South Sumatra - Rahima, Rahima; Susanto, Hardhono; Flora, Rostika; Bahrudin, Udin (Syntax Corporation Indonesia, 2023)
Fit physical condition is needed in every sport, especially in soccer which is known to be one of the dynamic sports with dominant movements using anaerobic energy, and also aerobic energy to be able to last throughout the game for a long duration. Every player is required to have excellent physical fitness which is certainly supported by maximum aerobic capacity. For an athlete, aerobic capacity is mandatory to be increased as much as possible, especially in adolescence, because at this time it can contribute to an increase in aerobic capacity of up to 30-35% compared to adults and the elderly, The purpose of this study was to determine the profile of the physical fitness level of athlete students through VO2Max parameters and Forced Vital Capacity / FVC lung in football athlete students at Sriwijaya State Sports School (SONS) Sumatra South. This type of research is a descriptive analysis and data collection is carried out by laboratory using a treadmill device with the Bruce method which is the gold standard in cardiopulmonary fitness assessment and a spirometry tool to measure the forced vital capacity of the lungs. The subjects in this study amounted to 33 male students from the sport of football. The results of the data analysis showed that the majority of SONS football athlete students had a fitness level with less category (96.9%) and very less category (3.1%), the predicted value of Forced Lung Vital Capacity with normal category was 66.7% and the remaining 33.3% in the category below normal. The average count (mean) of pulmonary FVC value is = 2.86 liters, with a maximum value of 3.82 liters and a minimum value of 1.46 liters. It can be concluded that the level of physical fitness in SONS soccer players is still low, for that it is necessary to increase the maximum aerobic capacity and lung capacity of athlete students as much as possible through an intense and systematic training program.